Agricultural Systems Management in The New Millennium - Schumacher, L.G.; Ess, D.R.; Strickland, R.M.; King, B.O. (Journal of Agricultural Systems, Technology, and Management, 2002)
Research was conducted to determine the current and future direction of Agricultural Systems Management programs across the nation. It was the intent of this study to determine the overall status of agricultural systems management programs in 1993 and 1999, compare this information to information gathered seven years earlier, and to gain insight concerning how these programs may change during the new millennium.